Medroxyprogesterone promotes neuronal survival after cerebral ischemic stroke by inhibiting PARthanatos - Yue, Chang-Ling; Ding, Yan-Xia; Chen, Meng; Shen, Yu-Xin; Hu, Ao-Meng; Huang, Hai; Zhang, Zhao-Huan; Zhou, Ying-Xin; Xu, Xiao-Hui (Frontiers in Pharmacology, 2025)
IntroductionCerebral ischemic stroke (CIS) is caused by the interruption of cerebral blood circulation due to thrombosis or embolism and is the second-leading cause of mortality worldwide. The neuronal death and motor dysfunction resulting from CIS are primarily attributed to the induction of PARthanatos in neurons at the site of ischemia. Blocking parthanatos is a promising treatment for CIS.MethodsThe effect of medroxyprogesterone treatment on PARthanatos in vitro was examined by CCK8 assay and flow cytometry and the target protein of medroxyprogesterone was then identified by a series of assays, including western blotting, immunofluorescence, cell thermal shift assay and molecular docking. Subsequently, the efficacy of medroxyprogesterone in the treatment of ischemic stroke was evaluated by FJC staining.ResultsIn our study, medroxyprogesterone was able to block the occurrence of PARthanatos in Hela cells induced by MNNG. PARP-1 activity did not change after medroxyprogesterone treatment but prevented MNNG-induced apoptosis inducing factor (AIF) release from mitochondria by improving the stability of phosphorylated extracellular signal-regulated kinase (ERK). In vivo, medroxyprogesterone significantly reduces neuronal death in mouse models of CIS by inhibiting PARthanatos.ConclusionOur findings indicate that medroxyprogesterone effectively inhibits PARthanatos not by affecting the activity of PARP-1, but by directly binding to ERK and stabilizes the active phosphorylated ERK, thereby inhibiting AIF translocation. Furthermore, medroxyprogesterone shows potential as a neuroprotective agent for patients with CIS, potentially enhancing post-stroke recovery and reducing societal burdens.